Multi-color live-cell super-resolution volume imaging with multi-angle interference microscopy. Issue 1 (December 2018) - Chen, Youhua; Liu, Wenjie; Zhang, Zhimin; Zheng, Cheng; Huang, Yujia; Cao, Ruizhi; Zhu, Dazhao; Xu, Liang; Zhang, Meng; Zhang, Yu-Hui; Fan, Jiannan; Jin, Luhong; et al.
Abstract Imaging and tracking of near-surface three-dimensional volumetric nanoscale dynamic processes of live cells remains a challenging problem. In this paper, we propose a multi-color live-cell near-surface-volume super-resolution microscopy method that combines total internal reflection fluorescence structured illumination microscopy with multi-angle evanescent light illumination. We demonstrate that our approach of multi-angle interference microscopy is perfectly adapted to studying subcellular dynamics of mitochondria and microtubule architectures during cell migration. 3D super-resolution imaging of dynamic processes in live cells is still challenging, especially in a large field of view. Here the authors combine SIM with multi-angle evanescent light illumination and achieve improved lateral and axial resolution, with stack acquisition time in the range of 1–2 s.